Determinants of Leprosy Prevalence in Sulawesi Island Using Spatial Error Model - Geraldi Putra P Balebu; Siskarossa Ika Oktora (Universitas Bumigora, 2022)
Leprosy is one of the infectious diseases and has become a serious health problem in Indonesia. Based on the publication of the Health Ministry of Republik Indonesia, there are still many areas in Indonesia that have not reached the leprosy elimination status, one of which is Sulawesi Island. The condition of leprosy prevalence in Sulawesi Island is still fluctuating and tends to be high. In addition, leprosy can also be spread across regions. This study aims to analyze whether a spatial effect is present on leprosy prevalence and determine the variables that possibly affect leprosy prevalence. Data used are from Health Profile and Province in Figure publications with an analysis unit consisting of 81 districts/cities. The results show that there is a spatial effect on leprosy prevalence in Sulawesi Island. Queen contiguity-based spatial weights are also considered while performing the spatial analysis. Based on the results of Spatial Error Models can be concluded that population density, the number of multibacillary (MB) leprosy cases, and spatial effect significantly affect the leprosy prevalence. In contrast, a clean and healthy lifestyle, proper water access, and proper sanitation access do not significantly affect the leprosy prevalence.